Dual assemblies of an activating immune receptor, MAIR-II, with ITAM-bearing adapters DAP12 and FcR gamma chain on peritoneal macrophages - 大越 靖; 本多 伸一郎; 渋谷 彰; 渋谷 和子; 大河内 信弘; Nakahashi Chigusa; Tahara-Hanaoka Satoko; Totsuka Naoya; Okoshi Yasushi; Takai Toshiyuki; Ohkohchi Nobuhiro; Honda Shin-ichiro; et al. (Journal of Immunology, 2007)
Certain activating immune receptors expressed on myeloid cells noncovalently associate with either DAP12 or Fc epsilon RI gamma (FcR gamma chain), the ITAM-bearing transmembrane adapter proteins. An activating receptor, myeloid-associated Ig-like receptor (MAIR) II, is expressed on a subset of B cells and macrophages in the spleen and peritoneal cavity of mice and associates with DAP12 in these cells. However, we demonstrate here that cross-linking MAIR-II with mAb induced secretion of a significant amount of the inflammatory cytokines TNF-alpha and IL-6 from DAP12(-/-) as well as wild-type (WT) peritoneal macrophages. We show that MAIR-II associates with not only DAP12 but also FcR gamma chain homodimers in peritoneal macrophages. LPS enhanced the FcR gamma chain expression and FcR gamma chain-dependent cell surface expression of MAIR-II and had additive effects on MAIR-II-mediated inflammatory cytokine secretion from peritoneal macrophages. The lysine residue in the transmembrane region of MAIR-II was involved in the association with FcR-y chain as well as DAP12. Our findings present the first case of an activating receptor that uses either DAP12 or FcRC gamma chain as a signaling adapter. The FcR-y chain may provide cooperation with and/or compensation for DAP12 in MAIR-II-mediated inflammatory responses by peritoneal macrophages.